Magnetic resonance and its applications in diagnostic imaging. - Méndez Colina, Pedro; Anaya Santacruz, Gerardo (Revista Mexicana de Ingenieria Biomedica, 1991)
Magnetic resonance imaging (MRI) is an interesting source of diagnostic information. This technology uses high magnetic fields and low energy radiofrequency signals to gather information from certain atomic nuclei in the body. The present notes describe some fundamental aspects about the operating principles of MRI, and how signals are generated to form images and how different parameters can be manipulated to obtain the most diagnostic information.